Adiponectin Isoforms Differentially Affect Gene Expression and the Lipidome of Primary Human Hepatocytes - Josef Wanninger; Gerhard Liebisch; Kristina Eisinger; Markus Neumeier; Charalampos Aslanidis; Lisa Voggenreiter; Rebekka Pohl; Thomas S. Weiss; Sabrina Krautbauer; Christa Buechler (Metabolites, 2014)
Adiponectin (APN) exerts multiple beneficial effects in obesity and protects from liver injury. Different APN isoforms circulate in serum, and here, the effect of low molecular weight (LMW) and higher molecular weight (HMW) APN on primary human hepatocytes (PHH) has been analyzed. APN is not detected in hepatocyte lysates; levels are strongly increased by HMW-APN, but not by LMW-APN, suggesting the distinct uptake/degradation of APN isoforms by PHH. Several genes with a role in fibrosis, glucose and lipid metabolism known to be regulated by HMW-APN are not affected by the LMW-isoform. Follistatin is reduced by HMW-APN and induced by LMW-APN in supernatants of PHH. Fibroblast growth factor 21 is repressed by both isoforms. Cellular triglycerides and cholesterol levels are not reduced by APN. Total phospholipids, including plasmalogens and sphingomyelins, are not changed upon APN incubation, while distinct species are either induced or repressed. Unexpectedly, total ceramide is increased by LMW-APN. Current data show that APN isoforms differentially affect hepatocyte gene expression, but do not grossly alter the hepatocyte lipidome.